DOES PERCEIVED COLLECTIVE EFFICACY MEDIATE THE DIAGNOSTIC BUDGET–TEAM EFFECTIVENESS LINK? EVIDENCE FROM HIGHER EDUCATION INSTITUTIONS IN WEST SUMATRA - Arisa Darlin; Imaniar; Zaitul (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
This study examines how the diagnostic use of budgets impacts team effectiveness in higher education institutions, particularly through the lens of psychological factors. While budgets are widely used as management control tools amid increasing demands for accountability and performance, there is limited and inconsistent empirical evidence on their effects on team outcomes. Drawing on Simons’ Levers of Control framework and Bandura’s Social Cognitive Theory, the research explores whether perceived collective efficacy serves as a mediator between diagnostic budget use and team effectiveness. Data were gathered from structural leaders and administrative staff involved in budgeting at higher education institutions in West Sumatra, Indonesia, yielding 59 valid responses, which were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results show that diagnostic budget use enhances both perceived collective efficacy and team effectiveness. Perceived collective efficacy, in turn, significantly boosts team effectiveness and partially mediates the link between budget use and team outcomes. These findings highlight the importance of psychological mechanisms—specifically, shared team confidence—in translating formal control practices into improved effectiveness. The study contributes to the management control literature by integrating management accounting and social-cognitive perspectives and recommends that universities support formal budget monitoring with measures to build collective team confidence, such as transparent feedback, participative goal setting, and recognition of team achievements.